SMARTPHONE USAGE AS A RISK FACTOR OF MYOPIA AMONG ELEMENTARY SCHOOL STUDENTS IN KEDIRI: Penggunaan Smartphone Sebagai Faktor Risiko Miopia Pada Anak Sekolah Dasar di Kota Kediri - Amanda Sari, Ladinna; Udijono, Ari; Sutiningsih, Dwi; Arie Wurjanto, Mohammad (Universitas Airlangga, 2025)
Background: Myopia is the inability to view distant objects. Most cases of myopia occur in school-age children. Working and studying from home due to the COVID-19 epidemic exacerbates myopia concerns. The Kediri City Health Office reports that school-age myopia cases rose in 2022. Purpose: This study aims to identify the risk factors of myopia related to smartphone usage among elementary school students in Kediri City. Method: This study is an observational study with a case-control approach. Random sampling is used in the sampling procedure. There were 144 participants: 72 students in the case group and 72 in the control group. Independent variables include smartphone duration, using a smartphone in a low-light environment, using a smartphone before sleep, and using a smartphone at an early age. Result: The study's findings revealed all factors were associated with myopia: smartphone duration (p-value = 0.001; OR = 4.5), using smartphone in low-light environment (p-value = 0.001; OR = 3.4), using smartphone before sleep (p-value = 0.001; OR = 3.3), and using smartphone in early age (p-value = 0.000; OR = 12. 4). Conclusion: This study shows that the duration of smartphone use of more than 3 hours increases the risk by 4.5 times, using a smartphone in low-light environment increases the risk by 3.4 times, using a smartphone before bed increases the risk by 3.3 times, and the risk of myopia increases 12.4 times for smartphone use at a younger age in elementary school students in Kediri City.